Hansel and Gretel - Robson; Kristeen (London Mind to Mind, 2010)
The story follows the siblings Hansel and Gretel, who are abandoned in the forest by their parents. They come across a gingerbread house owned by a wicked witch who plans to eat them. Using their cleverness and bravery, Hansel and Gretel outwit the witch, escape from her clutches, and find their way back home. The tale emphasizes themes of resourcefulness, sibling loyalty, and triumph over adversity.